3D Modeling and Simulation of Mass Transfer in Vapor Transport through Porous Membranes. Issue 1 (11th December 2012) - Shirazian, S.; Ashrafizadeh, S. N.
Abstract A 3D mathematical model is developed to predict the transport of water vapor through porous membranes. The model is based on solving the continuity, momentum as well as energy equations for water in the membrane contactor. The model's equations are numerically solved using the finite element method to obtain the concentration and temperature distributions of water in the membrane contactor. The model findings were in good agreement with experimental data. The proposed 3D model proved to be appropriate for predicting the performance of a membrane evaporator. Simulations were carried out in order to study the influence of different operating parameters and membrane structure on the membrane evaporation effectiveness. The results of simulation indicate that the gas velocity is a favorable parameter in the membrane evaporation process due to its tendency to keep the process far from the thermodynamic equilibrium.